2022
DOI: 10.52859/jba.v9i1.165
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Pemilihan Karir Sebagai Akuntan Publik

Abstract: The purpose of this study is to obtain empirical evidence regarding the effect of financial rewards, professional training, social values, professional recognition, work environment and market considerations on career interest as a public accountant. This study uses primary data with 137 respondents consisting of final year students in the S1 Accounting study program, Faculty of Economics and Business at Tarumanagara University. The results of the study found that in addition to the professional recognition va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…The data shows that there is minimal interest in Bachelor (S1) Accounting students in becoming a Public Accountant. This is confirmed by a statement by the Indonesian Institute of Public Accountants (IAPI) on CNN Indonesia which revealed that Indonesia still lacks public accountants, and data shows that 4.28% of public accountants in 700 companies on the SPT list in Indonesia require public accounting services(Viriany & Wirianata, 2022). The low number of public accountants in Indonesia indicate that Indonesia still needs many additional number of accounting professions, in order to anticipate the business sector growth, especially after Indonesia joined the Asean Economic Community (AEC) agreement in 2016…”
mentioning
confidence: 58%
“…The data shows that there is minimal interest in Bachelor (S1) Accounting students in becoming a Public Accountant. This is confirmed by a statement by the Indonesian Institute of Public Accountants (IAPI) on CNN Indonesia which revealed that Indonesia still lacks public accountants, and data shows that 4.28% of public accountants in 700 companies on the SPT list in Indonesia require public accounting services(Viriany & Wirianata, 2022). The low number of public accountants in Indonesia indicate that Indonesia still needs many additional number of accounting professions, in order to anticipate the business sector growth, especially after Indonesia joined the Asean Economic Community (AEC) agreement in 2016…”
mentioning
confidence: 58%
“…Fenomena pada profesi akuntan_publik di Indonesia menunjukkan jumlah akuntan publik di Indonesia cenderung rendah bila dibandingkan kebutuhan jasa di Indonesia, salah satunya yakni disebabkan karena kurangnya minat mahasiswa dalam Pemilihan Karir menjadi Akuntan Publik. Hal tersebut didukung oleh pernyataan Institut Akuntan Publik Indonesia (IAPI) pada CNN Indonesia yang mengungkapkan Indonesia masih kekurangan akuntan publik, dan data menunjukkan hanya 4,28 persen akuntan publik yang tersedia dari 700 perusahaan yang terdaftar SPT di Indonesia yang membutuhkan jasa akuntan publik (Viriany & Wirianata, 2022). Rendahnya jumlah akuntan publik di Indonesia ini menunjukkan bahwa Indonesia masih memerlukan profesi akuntan dalam jumlah besar, guna antisipasi bertumbuhnya sektor bisnis terutama setelah Indonesia mengikuti perjanjian Asean Economic Community (AEC) pada tahun 2016 (Warsitasari & Astika, 2017).…”
Section: Pendahuluanunclassified